Material evidence and narrative sources : interdisciplinary studies of the history of the Muslim Middle East - Talmon-Heller, Daniella; Cytryn-Silverman, Katia (Islamic history and civilization, 2015)
This book demonstrates the effectiveness of creative interdisciplinary research, applied to historical, cultural and archaeological problems in the study of the Middle East.